Multi-service Traffic for Mobile Broadband Systems in Presence of Mobility - Velez, Fernando J. (2001)
Multi-service traffic engineering will be a key aspect in cellular planning of Mobile Broadband Systems (MBS), allowing to obtain merit functions for optimisation purposes. MBS will serve applications via different service components, with different data rates and average durations, user mobility having impact on the handover failure probability threshold. While in the business city centre, and other urban scenarios, mobility has no significant effect, it affects the supported traffic in main roads; a reduction of 31 % existing in the 432 channel/cell case, relatively to the situation of absence of mobility.